2018
DOI: 10.1097/gox.0000000000001930
|View full text |Cite
|
Sign up to set email alerts
|

Skin Grafting on 3D Bioprinted Cartilage Constructs In Vivo

Abstract: Background:Three-dimensional (3D) bioprinting of cartilage is a promising new technique. To produce, for example, an auricle with good shape, the printed cartilage needs to be covered with skin that can grow on the surface of the construct. Our primary question was to analyze if an integrated 3D bioprinted cartilage structure is a tissue that can serve as a bed for a full-thickness skin graft.Methods:3D bioprinted constructs (10 × 10 × 1.2 mm) were printed using nanofibrillated cellulose/alginate bioink mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In general, they involve two concepts: cellular sources and biomaterials, including scaffolds and hydrogels. Onofrillo [33], Apelgren et al [31], and Leberfinger [24] prioritized the need to develop protocols for obtaining cells; they also recognized that, despite variable sources, all cells must maintain chondrogenic capacity, not cause morbidity at the donor site, expand easily in the culture without losing phenotype, and support the mechanical load in the joint case. Di Bella et al [34], You et al [35], and Wu et al [25] presented disparate technical aspects that should be improved, since they followed different research paths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, they involve two concepts: cellular sources and biomaterials, including scaffolds and hydrogels. Onofrillo [33], Apelgren et al [31], and Leberfinger [24] prioritized the need to develop protocols for obtaining cells; they also recognized that, despite variable sources, all cells must maintain chondrogenic capacity, not cause morbidity at the donor site, expand easily in the culture without losing phenotype, and support the mechanical load in the joint case. Di Bella et al [34], You et al [35], and Wu et al [25] presented disparate technical aspects that should be improved, since they followed different research paths.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical application studies focused on certain surgical approaches and identified specific technical improvements needed to obtain better results; improvements included an algorithm to ensure that the nasal implant is not degraded or subjected to excessive long-term pressure [29]; a process to guarantee the characteristics of the skin of the ear in plastic surgery [31]; and in otorhinolaryngology, the use of a membrane trachea coating and image processing to optimize surgical results [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSC three-dimensional (3D) bioprinting is an emerging technology that is expected to revolutionize the field of regenerative medicine [6,20,[38][39][40], including hyaline articular cartilage engineering [41][42][43][44][45][46][47][48][49][50][51][52]. Previous tissue engineering approaches for cartilage repair usually failed to generate functional tissues recapitulating the zonal organization, extracellular matrix (ECM) content, and biomechanical properties of native cartilage.…”
Section: Discussionmentioning
confidence: 99%